2012
DOI: 10.1080/02188791.2012.655237
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Chinese students in an Australian university: are we meeting their needs?

Abstract: This short-term longitudinal study sought to identify the issues faced by a group of international Chinese students undertaking study in an Australian university. While the focus was on educational issues, socio-cultural and personal factors were also examined in an attempt to identify the sorts of strategies students used in settling into a new socio-cultural and educational context. Interviews conducted at the beginning and end of the first semester of study indicate a range of issues that are supported by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Social connection is also an important factor according to the analytical results of the 68 reviewed articles. Pursuing intercultural communication in English language is an important aspect for Chinese students when they determine to study abroad, so Australian context and Australian culture can provide the opportunities for Chinese students (Briguglio & Smith, 2012). Besides, Chinese students increasingly pay attention to social connections of alumni and see classmates as an important factor when choosing Australian universities (Xu & Xu, 2018).…”
Section: Study Languagementioning
confidence: 99%
“…Social connection is also an important factor according to the analytical results of the 68 reviewed articles. Pursuing intercultural communication in English language is an important aspect for Chinese students when they determine to study abroad, so Australian context and Australian culture can provide the opportunities for Chinese students (Briguglio & Smith, 2012). Besides, Chinese students increasingly pay attention to social connections of alumni and see classmates as an important factor when choosing Australian universities (Xu & Xu, 2018).…”
Section: Study Languagementioning
confidence: 99%
“…The Chinese curriculum focuses heavily on the technical knowledge required to pass examinations (Gu, ), thereby explicitly excluding a western perspective of employability skills (Henderson, ). Nevertheless, despite transition challenges, language difficulties and the inevitable culture shock experienced by Chinese students on arrival in Australia (Briguglio and Smith, ), research has shown that these students have a remarkable ability to adapt quickly to western culture, learning styles and expectations (Yan and Berliner, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Australia has one of the most internationalised higher education sectors in the world with more than 20 percent of enrolments comprising international students (Walters, ). Since 2004, the greatest demand for international education has come from China (Briguglio and Smith, ), with Australia currently ranking the third most popular destination for Chinese students after the United States and Japan (AEI, ). In the UK, Canada and New Zealand, Chinese students also significantly outnumber all other groups of international students (Choudaha et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority came from Asia -China (65%) and Hong Kong (10%). Within a broader educational context, the strong presence of Asian students in the international student cohort both in Australia and overseas is noted in the literature (Birguglio & Smith, 2012;Gu & Schweisfurth, 2006;Jin & Cortazzi, 2011) as highly significant in international education. "Affluence, economic growth, values strongly supportive of education and uncertainties about domestic capacity all contribute to Asia's growing presence in global student mobility" (Kell & Vogl, 2012, p.13).…”
Section: Profile Of International Studentsmentioning
confidence: 99%